The implementation of six sigma DMAIC in evaluation of direct booking improvement strategy at Alpha hotel management - Putri, Ni Putu Widya Maheswari Karantika; Utama, I Putu; Darmawijaya, I Gede (Jurnal Pariwisata Pesona, 2025)
The management of room source of bookings (SOB) plays a crucial role in the hospitality industry as it directly impacts hotel profitability. A significant challenge faced by Alpha Hotel Management (AHM) is the dominance of Online Travel Agents (OTAs), contributing up to 80% of total bookings, while direct bookings only account for 12%, far below the 30% target. This high dependency on OTAs not only reduces profit margins due to high commission fees but also limits the hotel’s direct engagement with guests. This study aims to develop strategies to increase direct bookings through website optimization using the Six Sigma DMAIC approach (Define, Measure, Analyze, Improve, Control). The study revealed key issues such as limited room allotment, low website visibility, lack of early bird programs, and suboptimal website performance as major factors hindering direct bookings. After implementing strategies like SEO optimization, Google Ads, website redesign, and staff training, significant improvements were observed, with conversion rates increasing by up to 181%. These improvements were accompanied by a marked increase in visitor interactions and direct bookings across AHM’s properties. Further developments such as loyalty programs and flexible payment systems are expected to enhance website performance and reduce reliance on OTAs. Continuous monitoring and adaptive strategies are essential for achieving sustained growth in direct bookings and enhancing hotel profitability.